2016
DOI: 10.1007/s12272-016-0767-z
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity of intravenously injected zinc oxide nanoparticles in rats

Abstract: Recent toxicity studies of zinc oxide nanoparticles by oral administration showed relatively low toxicity, which may be resulted from low bioavailability. So, the intrinsic toxicity of zinc oxide nanoparticles needs to be evaluated in the target organs by intravenous injection for full systemic concentration of the administered dosage. Although the exposure chance of injection route is low compared to oral and/or inhalation route, it is important to see the toxicity with different exposure routes to get better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Previous research on metal oxidative NPs found developmental toxicity induced by nano-silver ( Xin et al, 2015 ; Charehsaz et al, 2016 ; Ema et al, 2017 ; Pecoraro et al, 2017b ), nano-silica ( Yi et al, 2016 ), graphene oxide ( Buccheri et al, 2016 ; Pecoraro et al, 2017a ), zinc oxide ( Bonfanti et al, 2015 ; Zhou et al, 2015 ; Lee et al, 2016 ; Spence et al, 2016 ), iron oxide ( Di Bona et al, 2015 ), copper oxide ( Maisano et al, 2015 ; Ganesan et al, 2016 ; Torres-Duarte et al, 2016 ), magnesium oxide ( Ghobadian et al, 2015 ), titanium dioxide ( Scuderi et al, 2014 ; Parivar et al, 2015 ; Rollerova et al, 2015 ; Brundo et al, 2016 ), and cerium oxide ( Andersen et al, 2016 ). Moreover, studies have shown that bulk-Al, once entering the brain, persists for a very long time with a half-life ranging from 20% of the lifespan to greater than the entire lifespan ( Yokel, 2000 , 2002 ; Priest, 2004 ; Exley and House, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on metal oxidative NPs found developmental toxicity induced by nano-silver ( Xin et al, 2015 ; Charehsaz et al, 2016 ; Ema et al, 2017 ; Pecoraro et al, 2017b ), nano-silica ( Yi et al, 2016 ), graphene oxide ( Buccheri et al, 2016 ; Pecoraro et al, 2017a ), zinc oxide ( Bonfanti et al, 2015 ; Zhou et al, 2015 ; Lee et al, 2016 ; Spence et al, 2016 ), iron oxide ( Di Bona et al, 2015 ), copper oxide ( Maisano et al, 2015 ; Ganesan et al, 2016 ; Torres-Duarte et al, 2016 ), magnesium oxide ( Ghobadian et al, 2015 ), titanium dioxide ( Scuderi et al, 2014 ; Parivar et al, 2015 ; Rollerova et al, 2015 ; Brundo et al, 2016 ), and cerium oxide ( Andersen et al, 2016 ). Moreover, studies have shown that bulk-Al, once entering the brain, persists for a very long time with a half-life ranging from 20% of the lifespan to greater than the entire lifespan ( Yokel, 2000 , 2002 ; Priest, 2004 ; Exley and House, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…, poly(glycidyl methacrylate) (PGMA), and PS) (Table 3 ). Fetal/embryonic NP accumulation was observed in 32 of the included animal studies, more specifically NPs were detected in the fetal brain [ 27 , 44 , 48 , 52 , 60 , 73 , 78 , 80 , 81 , 91 ], fetal liver [ 27 , 48 , 50 , 52 , 60 , 69 , 73 , 83 , 84 , 86 ], fetal lung [ 27 , 48 , 52 , 75 ], fetal kidney [ 48 , 52 , 84 ], fetal gastrointestinal tract (GIT) [ 88 ], and fetal blood [ 92 ]. The preferred method for NP administration was intravenous (i.v.)…”
Section: Resultsmentioning
confidence: 99%
“… [ 82 ] Sprague Dawley rats 4 ZnO NPs/ citrate 20 a oral/ 0 or 400 mg/kg/ GD5–19 d ICP-OES / No significant difference in fetal Zn content between control and ZnO NP exposed group. [ 83 ] Sprague Dawley rats 10 ZnO NPs/ APTES > 35 a i.v./ 0 or 20 mg/kg/ GD6–20 d ICP-MS / Significantly elevated Zn levels in fetal liver after IV injection of pregnant rats with ZnO NPs. [ 84 ] Sprague Dawley rats 24 ZnO NPs < 100 a oral/ 0 or 500 mg/kg/ 14 days before mating-day 4 of lactation g ICP-MS / Significantly higher levels of Zn in liver and kidneys, but not in blood and brain of rat offspring exposed to ZnO NPs before, during, and after gestation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pregnancy stage, harmful effects of new products such as those containing ZnO NPs, affect the reproductive route inducing fetal malformation or even fetal death. Recently, some researches showed that ZnO NPs could cause reproductive and development toxicity, but insufficient studies had been devoted to determination of the internal mechanism involved in the reproductive toxicity of ZNOs [7,18,19].…”
Section: Discussionmentioning
confidence: 99%